2017
DOI: 10.1530/eje-16-1037
|View full text |Cite
|
Sign up to set email alerts
|

Associations between serum levels of calcium, parathyroid hormone and future risk of venous thromboembolism: the Tromsø study

Abstract: Serum levels of calcium and PTH separately were not associated with future risk of VTE, but subjects with high levels of both calcium and PTH had increased risk of VTE compared to those in subjects with normal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…by SKAT analysis do not provide directionality, but the risks of embolism/ thrombosis and diastolic heart failure have been shown to be influenced by serum Ca concentrations; 32,33 likewise, neuropsychiatric disorders have been associated with serum Ca concentrations in small case-control studies. 34,35 CaSR is widely expressed in the cardiovascular 36,37 and nervous 38 systems, and it remains to be determined whether these disease associations result from elevated serum Ca concentrations, reduced CaSR function, or both.…”
Section: Discussionmentioning
confidence: 99%
“…by SKAT analysis do not provide directionality, but the risks of embolism/ thrombosis and diastolic heart failure have been shown to be influenced by serum Ca concentrations; 32,33 likewise, neuropsychiatric disorders have been associated with serum Ca concentrations in small case-control studies. 34,35 CaSR is widely expressed in the cardiovascular 36,37 and nervous 38 systems, and it remains to be determined whether these disease associations result from elevated serum Ca concentrations, reduced CaSR function, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, increased serum PTH concentrations due to vitamin D insufficiency might lead to low arterial compliance and high stiffness, resulting in increased CVD. High PTH was also associated with increased risk of heart failure and venous thromboembolism [ 39 , 40 ]. Clinical research has indicated that early treatment of parathyroid disorders may reverse cardiovascular remodeling and mitigate cardiac risk factors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, among 27,685 subjects (25-87 years) participating in Tromsø 4 (1994Tromsø 4 ( -1995 and 8547 individuals participating in Tromsø 5 (2001Tromsø 5 ( -2002 surveys, where total calcium and PTH were measured, 712 cases of venous thromboembolism (VTE) were documented during a median follow-up of 15 years. Subjects with high serum levels of both calcium and PTH (calcium ≥2.45 mmol/L and PTH ≥4.0 pmol/L) had an increased risk of VTE compared to that in subjects with normal calcium and PTH values (multivariable HR: 1.78, 95% CI: 1.12-2.84) [16]. These studies support a correlation between calcium levels and enhanced activation of the coagulation system.…”
Section: Discussionmentioning
confidence: 58%